2009
DOI: 10.1177/1079063208328677
|View full text |Cite
|
Sign up to set email alerts
|

Applying Rapid Serial Visual Presentation to Adolescent Sexual Offenders

Abstract: Attentional bias toward child images is assessed among adolescent sexual offenders and nonsexual offenders using the rapid serial visual presentation (RSVP) method, which measures the effects of "attentional blink." Twenty adolescent sexual offenders against children and 26 nonsexual offenders are asked to identify a child or animal image and then a second image in streams of 10 images. A stronger attentional blink effect is expected for offenders against children after viewing child rather than animal images.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, Crooks et al. ( 2009 ) have questioned the use of rapid serial visual presentation of child or animal images in adolescent sexual offenders: adolescent cognitive abilities may not be able to allow them to concentrate on the task and deviant sexual interest may be present to different degrees in adolescents. In fact, its use as an outcome measure with adolescents is a subject of controversy among professionals as no normative data exist for adolescents.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…However, Crooks et al. ( 2009 ) have questioned the use of rapid serial visual presentation of child or animal images in adolescent sexual offenders: adolescent cognitive abilities may not be able to allow them to concentrate on the task and deviant sexual interest may be present to different degrees in adolescents. In fact, its use as an outcome measure with adolescents is a subject of controversy among professionals as no normative data exist for adolescents.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Beech et al (2008) used a rapid serial visual presentation task and found an interference effect for child images in a group of child sex offenders. However, recently the task has failed to significantly differentiate between juvenile sex offenders and non-sex offenders (Crooks, Rostill-Brookes, Beech, & Bickley, 2009). Snowden, Wichter, and Gray (2008) compared the implicit association task (IAT) and the priming task (PT) in a group of heterosexual and homosexual men and found that both measures were good predictors of sexual orientation, although the IAT (area under a receiver operating characteristic curve [AUC] = 0.97) performed better than the PT (AUC = 0.86).…”
Section: Information Processing Tasksmentioning
confidence: 99%
“…Crooks et al . () assessed AB among 20 adolescent sex offenders and 26 non‐sex offenders using RSVP. The participants were asked to identify a child or animal image and then a second image in streams of ten images.…”
Section: Introductionmentioning
confidence: 99%
“…Using contrast analyses, they found a significant difference between the control group and the intra-familial child molester sample (p < 0.01, effect size = 0.45, and the control group and the extra-familial child molester group, p < 0.001, effect size = 0.54). Crooks et al (2009) assessed AB among 20 adolescent sex offenders and 26 non-sex offenders using RSVP. The participants were asked to identify a child or animal image and then a second image in streams of ten images.…”
Section: Introductionmentioning
confidence: 99%